(untitled) (Journal of Interdisciplinary Insights, 2024)
During the implementation of CPEC in Pakistan, there have been attacks by terrorist organizations, particularly threats from Baloch separatists and the Pakistani Taliban, leading to frequent assaults on Chinese citizens and infrastructure. Additionally, the domestic turmoil and border disputes in Afghanistan have created significant obstacles to the extension of CPEC into Afghanistan. The security situation along the Afghanistan-Pakistan border is complex, and Afghanistan’s unstable political, economic, and social environment has heightened the risks to the development of CPEC in the region.